Simulation Study of Divided Wall Distillation Column - Kaur, Lovedeep (My University, 2012)
Separations performed in distillation columns are responsible for largest fraction of immense amount of energy consumed in process industries. Application of non-standard complex column arrangements can lead to substantial savings in energy consumption. Among these alternatives, dividing-wall columns (DWCs) for separating mixtures of three or more components appear to be the most attractive as they provide substantial savings in both energy consumption as well as capital investment. Dividing wall column (DWC) is a single shell, fully thermally coupled distillation column capable of separating mixtures of three or more components into high purity products. Compared to conventional columns-in-series and/or in-parallel configurations, a DWC requires much less energy, capital and space. This makes DWC to something that corresponds with the present day idea of sustainable process technology. The simulation of a non-standard column like DWC is more complex than that of a conventional distillation as there are more degrees of freedom involved and more parameters to be manipulated. Simulation studies were done in ASPEN but it does not include a DWC in its library operations. Hence, DWC is simulated based on the configuration of fully thermally coupled column, called Petlyuk column. The MultiFrac model of ASPEN Plus™ has been used For rigorous simulation. The purpose of this study was to investigate the effects of structural and operational variables on product purities, reboiler duty and pressure across the divided wall for C4, C5, and C6 ternary separation in a DWC. The structural variables such as feed location, side location, number of stages in main column and in postfractionator and liquid and vapor split locations have no significant effect on reboiler duty, but the position of divided wall have a small effect on energy efficiency of DWC. The liquid and vapour split locations affects the side stream purities more as compared to top and bottom product purities. The pressure drop across the divided wall is greatly affected by varying liquid and vapor split locations towards the bottom of the column. The operational variables liquid split ratio and vapour split ratio affects the side stream purity significantly as compared to distillate and bottom product purities. The operational variables, reflux ratio and vapour split shows a great effects on pressure drop across the divided wall as compare to liquid split ratio. The operational variables such as reflux ratio, liquid split and vapor split ratio have a great affect on the reboiler duties. The thermodynamic efficiency of DWC is 28.3% more than the columns in direct sequence. The total annualized cost of DWC is 28% less than the column in direct sequence.
Keywords: Simulation Study; Wall Distillation Column